Oxygen in the Earth System - Klemens Hocke (Oxygen, 2023)
Atmospheric oxygen is produced and consumed by life on Earth, and the ozone layer protects life on Earth from harmful solar UV radiation. The research on oxygen in the Earth system is of interest to many different geoscientific communities, from paleoclimatology to aeronomy. I provide a brief overview of the research activities and their motivations. In situ measurements and remote sensing of atmospheric oxygen are described. The global evolution, distribution, and trends of atmospheric oxygen are discussed.